TELAAH KRITIS: KEGAGALAN PENEGAKAN HUKUM PIDANA KEJAHATAN PERDAGANGAN ORANG - Heni Siswanto (Masalah-Masalah Hukum, 2013)
Criminal law enforcement against the human trafficking crimes not integral and quality yet, either in abstracto or in concreto still weaknesses. Weakness due to: (1) placement some of criminal law legislation against the human trafficking crimes partially; point of view of law enforcement officer of the matter the human trafficking crimes is not same dangerously; interagency coordination of lawenforcement officer to achieve three key issues of criminal law is still weakness. (2) not qualified yet tinged foul play among law enforcement officers. (3) not optimalization yet to use of scientific approach in order to produce a quality legal product.